Nanopore-based Strategy for Selective Detection of Single Carcinoembryonic Antigen (CEA) Molecules - Tang, Haoran; Wang, Hao; Yang, Cheng; Zhao, Dandan; Qian, Yuanyuan; Li, Yongxin (Analytical chemistry (Washington), 2020)
Nanopores have become one of the most important tools for single-molecule sensing, but the challenge for selective detection of specific biomolecules still exists. In this contribution, we develop a new technique for sensing carcinoembryonic antigen (CEA), one of the important cancer biomarkers, using solid-state nanopores as a tool. The method is based on the specific affinity between aptamer (Apt) modified magnetic Fe3O4–Au nanoparticles (MNPs) and CEA, and the formed CEA–Apt–MNPs and remaining Apt–MNPs can transport the nanopores by applying a positive potential after magnetic separation. Due to the obvious particle size difference between CEA–Apt–MNPs and Apt-MPs, their corresponding blockage signals could be distinguished completely by the degree of the current decline. Moreover, the frequency of the blockage signals for CEA–Apt–MNPs is proportional to the concentration of CEA within certain limits, indicating that our designed nanopore sensing strategy can quantitatively detect CEA in complex samples. This work demonstrates that our designed nanopore-based strategy can be used for CEA sensing with good selectivity and sensitivity and also can be used to analyze other protein biomarkers for early diagnosis and monitoring of cancer, though the detection limit (0.6 ng/mL) is not relatively low. In future works, we plan to improve our detection limit by the improvement of the nanopipette preparation technology and detection method.